Environmental Education in the Place of Interest and with the Participation of the People Involved - Batres Quevedo, Jorge Alejandro (2020)
Since its origins, environmental education has gone through three stages: in the 1970s its most important dimensions, purposes and intentions were defined; in the 1980s the concept of sustainability was integrated and in the 1990s it was contingent on the purposes of sustainable development. In the following years, a new trend is not identified, but its most important problems are visible: institutionalization, schooling and environmental activism. In order to contribute to the solution of these and other identified problems, this article presents the results of an experience of a participatory approach, originated in community work and teaching practice, called Situated Environmental Education. The experience seeks to fulfill three purposes: to promote the use of participatory methodologies to solve, in part, schooling and institutionalization; to conceive environmental education as a comprehensive, well-located and meaningful educational process that transcends environmental activism, and to promote an environmental ethics of responsibility in the human-nature relationship. The most important result of the conceptual framework of located education is the validation of a methodology to educate environmentally in specific places and with the participation of the people involved.